Act on Support and Resocialization of Minors from the Perspective of Contemporary Trends in Dealing with Minors - Irena Mudrecka (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: On September 1, 2022, the Act on Support and Resocialization of Juveniles entered into force, which replaced the almost 40-year-old Act on Proceedings in Juvenile Cases, which was already considered outdated and inadequate to the realities of the 21st century. Research Aim: The aim of the presented considerations is to interpret selected provisions of the Act on the Support and Resocialization of Juveniles from the perspective of social rehabilitation practice. The issue concerns whether the current legal regulations regarding minors are preventive measures in dealing with minors. In addition, it is important to spread knowledge about new rules for proceedings with minors in order to raise the legal awareness of society, especially educators, teachers and parents, because they are obliged to educate children and young people in this matter, otherwise the law does not fulfill its preventive function. Evidence-based Facts: The new Act on Support and Resocialization of Juveniles duplicates the provisions of the Act on Proceedings in Juvenile Matters in many places. However, there are changes that can be called fundamental. These include the introduction of a lower limit of responsibility for minors, lowering the age of criminal responsibility for minors for the most serious crimes, the possibility of extending the duration of correctional measures in specific situations, the creation of district educational centers, equipping school principals and bodies conducting explanatory proceedings with the competence to use educational measures. Summary: The assessment is not clear, as the new regulations introduce rules corresponding to the retributive model. In addition, the legislator maintained elements of the care model and the restorative justice model. The act also includes provisions that can be assessed as introducing elements of the diversion system.